Epidemiology of oxacillin-resistant staphylococcus aureus from cell phones of health-care workers in Ekiti State - Oluwole, Olusola; David, Oluwole; Owolabi, Ayomide (International Journal of Scientific World, 2016)
The use of mobile phones in the clinical environment by health-care workers has become widespread. A swab of mobile phones of health-care personnel of several hospitals in Ekiti State were examined to evaluate the prevalence of Oxacillin resistant Staphylococcus aureus (ORSA), the resistance of ORSA to other commonly used antibiotics as well as the multiple resistant patterns of the recovered isolates. A total of 106 samples were screened yielding 100 S. aureus isolates. The antibiotics sensitivity profile to nine commonly used antibiotics revealed high levels of resistance amongst the isolates ranging from 47% resistance to Chloramphenicol to 100% resistance exhibited to cloxacillin with 55% of the isolates showed resistance to oxacillin while all isolates exhibited multiple resistance. Also, all 55 ORSA exhibited 100% resistance to erythromycin and cloxacillin but interestingly were very sensitive (99.9%) to gentamycin. The high recovery rate of bacteria from mobile phones revealed that cell phones may have notable roles in the transmission of multidrug resistant nosocomial pathogens, increasing the risk of cross-contamination posed to immunosuppressed patients by the heath care workers attending to them.